Rosenberg versus 20/10 Views in Osteoarthritic Knees - Tait, Mark A.; Newbern, Gordon D.; Alexander, Albert S.; Barnes, C. Lowry (The Journal of Knee Surgery, 2013)
It has become a common practice to obtain weight-bearing radiographs for the assessment of early-stage osteoarthritis of the knee, and weight bearing with the knee in full extension has been the most common method. Other methods for evaluating knee joint space using weight-bearing radiography include the Rosenberg and 20/10 views. Eighty consecutive patients with knee pain were evaluated with standing Rosenberg and standing 20/10 views as part of their radiographic evaluation. The joint space for the right and left knee of each patient was measured. There was no statistically significant difference between the measurements for the 20/10 or Rosenberg views in left or right knees. We found no indication to additionally include 20/10 views in routine examinations of osteoarthritic knees when Rosenberg views had been obtained.
Keywords: Rosenberg view; 20/10 view; weight-bearing radiographs; joint space; knee osteoarthritis